Pengenalan Aktivitas Manusia Melalui Analisis Data Gerakan Smartphone - Eunike Endariahna Surbakti; Andes Suciani; Philipus Silaen; Septian Adibowo (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
Abstract− Today's smartphones are not only a means of communication but now offer many features and deployment of sensors. Smartphones are also designed to track the user's daily activities, learn and then help the user to make better decisions about what the user will take in the future. Applications that utilize the movement of a smartphone to analyze human activity are used by the Moves app, Fitbit Charge, Nike Fuelband, Apple Watch Health app. To perform human motion recognition activities, data is generated and collected from smartphones such as iPhones and Androids, or wearables such as the Apple Watch smartwatch, Nike Fuelband, and Fitbit Charge. Sensors commonly used to collect data include an accelerometer, gyroscope, heart rate monitor, and thermometer. Another method also combines these sensors with a magnetometer and GPS. This study compares previous research to seek opportunities from the resulting benefits such as monitoring city prisoners, community grouping, city density detection and distribution maps whose data can be used by business opportunities. Keywords: Accelerometer, Human movement recognition activity, Gyroscope, Heart rate monitor, Thermometer.